Confronting COVID-19 Myths: Morbidity and Mortality - Pavel Jelnov (Global Labor Organization (GLO), 2020)
COVID-19 mystery feeds the belief that the reported morbidity rates are not related to the true ones and that large parts of the population are already infected, the virus is not very dangerous, and the lockdown is unnecessary. Yet one observes two very strong correlations that disprove this belief. The cross-country correlation between log of tests and log of reported cases (per capita) is 0.87 and the correlation between log of reported cases and log of reported deaths (per capita) is 0.89. Using these correlations, I suggest that the infection rate in no country is higher than 10%. Furthermore, I suggest that the mortality from COVID-19 is at least 0.4%.
Keywords: I18; 330; COVID-19 morbidity; COVID-19 mortality